Incidence and Clinical Outcomes of Hip Fractures Involving Both the Subcapital Area and the Trochanteric or Subtrochanteric Area. (4th April 2019) - Tani, Takayuki; Kijima, Hiroaki; Konishi, Natsuo; Kubota, Hitoshi; Yamada, Shin; Tazawa, Hiroshi; Suzuki, Norio; Kamo, Keiji; Okudera, Yoshihiko; Fujii, Masashi; Sasaki, Ken; Kawano, Tetsuya; et al.
Abstract : Purpose . Proximal femoral fractures involving both the subcapital area and the trochanteric or subtrochanteric area have rarely been reported, but they are not uncommon. However, few studies have reported the incidence or clinical outcomes of such fractures. This study investigated such fractures. Methods . In area classification, the proximal femur is divided into 4 areas by 3 boundary planes: the first plane is the center of femoral neck; the second plane is the border between femoral neck and femoral trochanter; and the third plane links the inferior borders of greater and lesser trochanters. A fracture only in the first area is classified as a Type 1 fracture; one in the first and second areas is classified as a Type 1- 2 fracture. Therefore, proximal femoral fractures involving both the subcapital area and the trochanteric area are classified as Type 1- 2-3, and those involving both the subcapital area and the subtrochanteric area are classified as Type 1- 2-3-4. In this study, a total of 1042 femoral proximal fractures were classified by area classification, and the treatment methods and the failure rates were investigated only for Types 1- 2-3 and 1-2-3-4 cases. The failure rate was defined as the incidence of internal fixator cut-out or telescoping >10 mm. Results . Types 1- 2-3 and 1-2-3-4 fractures accounted for 1.72%. Surgical treatment was performed for 89%. Of these, 56% underwent osteosynthesis, but the failure rate was 33%. The other patients (44%) underwent prosthetic replacement. Fracture lines of all these fractures were present along trochanteric fossa to intertrochanteric fossa in posterior aspect and just below the femoral head in anterior aspect. Conclusion . Fracture involving the subcapital area to the trochanteric or subtrochanteric area was found in approximately 2%. In patients for whom prosthetic replacement was selected, good results were obtained. However, 1/3 of patients who underwent osteosynthesis had poor results.